ANALISIS ORIENTASI KEPEMIMPINAN PADA KINERJA KARYAWAN DI SEKTOR PELAYANAN KESEHATAN (Studi Di Klinik Husada Jombang) - Yastutik, Iryani Yuni; Febrianto, Kiki; Shomad, Miftahus; Semi (LPPM STIKES HUSADA JOMBANG, 2024)
Research on the influence of leadership orientation on employee performance in the health services sector, with a case study at the Husada Jombang Clinic. Effective leadership has been shown to have a significant impact on the performance of healthcare organizations. Using a quantitative approach, this research involved 100 employees of the Husada Jombang Clinic as respondents. Data was collected through a structured questionnaire that measured employee perceptions of leadership orientation and self-report performance. Data analysis was carried out using multiple regression methods and path analysis to test the relationship between variables. The research results show that transformational leadership orientation has a significant positive influence on employee performance (β = 0.45, p < 0.01). Mediation analysis reveals that work motivation acts as a partial mediator in the relationship between leadership orientation and employee performance. This research provides a theoretical contribution by expanding understanding of the mechanisms through which leadership orientation influences performance in the context of health services in Indonesia. Practically, these findings can be used by health leaders to develop more effective leadership strategies to improve employee performance and service quality.